Effects of a twisted magnetic rope at the stage of the appearance of a new active region in the photosphere - Grigoryev Victor; Ermakova Lyudmila (Solar-Terrestrial Physics)
Using SDO/HMI data, we have studied the dynamics of small-scale magnetic field elements in the photosphere during the formation of small active region USAF/NOAA 12761. The choice of this region is due to the fact that it formed near the central meridian at the minimum of the 11-year solar activity cycle in the absence of strong background magnetic fields. It has been established that two days before the formation of the first pores, the initially observed small-scale structure of the magnetic field forms chains of elements of both polarities. The structure of the chains creates a stable polarity dividing line (PIL). During the first day, the orientation of PIL changes from quasi-latitudinal to quasi-meridional. After comparing observations with a number of theoretical models, we concluded that the observed dynamics of elements of magnetic chains is consistent with the models of emergence of a magnetic flux rope in the photosphere.